Arsenic present in the soil‐vine‐wine chain in vineyards situated in an old mining area in Trentino, Italy. (21st February 2013) - Bertoldi, Daniela; Villegas, Tomás Román; Larcher, Roberto; Santato, Alessandro; Nicolini, Giorgio
Abstract: The present study follows arsenic (As) transfer through the chain of soil‐vine‐leaves‐grapes‐wine to assess the possible risk of arsenic intake related to consuming grapes and wines produced in 10 vineyards located in a mining area rich in this element. The results are compared with date from 18 uncontaminated areas. In the soil, the content of As extracted with acqua regia and that extracted with ammonium acetate, were analyzed. Leaves and berries were analyzed after washing with acidified aqueous solution and acid mineralization in a closed vessel, whereas wines were simply diluted before analysis. All analyses were performed using an inductively coupled plasma mass‐spectrometer. The aqua regia extractable As concentration in soil ranged from 3.7 to 283 mg/kg, whereas available As varied from 18 to 639 µg/kg, and As total concentration ranged from 16.3 to 579 µg/kg dry weight in leaves and from <0.1 to 36.8 µg/kg dry weight in grapes. Arsenic levels in wines were always below 1.62 µg/L, with higher concentration in red wines than in white wines. Significant and positive correlations between the As concentrations in soils, leaves, and berries are highlighted, with the samples collected near the mining area having significantly higher values. Nevertheless, As levels in wines were always well below the limit (200 µg/L) suggested by the International Organization of Vine and Wine. Environ. Toxicol. Chem. 2013;32:773–779. © 2013 SETAC